Meningkatkan Minat Pelaku Usaha Ultra Mikro untuk Berkoperasi: (PKM pada Pelaku Usaha Ultra Mikro di Kawasan Pendidikan Tinggi Jatinangor) - Indriani, Yuanita (E-Coops-Day, 2025)
The changes and developments of Jatinangor began to occur since the establishment of various universities in the Jatinangor Higher Education area, namely the Indonesian Cooperative University, the National Government College, Padjadjaran University and the Bandung Institute of Technology, Jatinangor Campus. Regional development has had an impact on Jatinangor's social and cultural changes, this area has become a relatively open area, residents from various parts of Indonesia have come, which has also had the impact of growing various business opportunities, including business opportunities for ultra-micro business actors operating in various. The businesses most in demand by the public are food and beverage businesses with a target market of students, workers in various businesses supporting educational areas, construction workers and other communities. One of the weaknesses of ultra-micro business actors is limited access, which is triggered by various conditions, including the lack of knowledge of business actors to be able to access information, access to sources of financing, innovation and technology. These limitations result in ultra-micro business actors becoming weak and uncompetitive, very vulnerable to change, their businesses do not develop, frequently change commodities and often experience bankruptcy. In fact, Jatinangor's rapid development as a higher education area should be an example of inclusive regional development, which also improves the welfare of its people. One solution to reduce the limitations that result in the non-development of ultra-micro business actors is to build togetherness between them so that they become a force that can change towards improvement; For this reason, an economic forum for business actors is needed which is driven by students and facilitated and encouraged by village officials. An economic forum that suits the needs of business actors to progress and develop is a cooperative. For this reason, it is necessary to initiate the introduction of cooperatives to ultra-micro business actors in Jatinangor.